PENGARUH MANAJEMEN LABA, STRUKTUR KEPEMILIKAN, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - LISA FRANSISKA; ARIES JONATHAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain an empirical evidence about the influence of profitability, leverage, liquidity, firm size, dividend policy, tangibility, company growth, institutional ownership, managerial ownership, and earnings management on firm value. The population used in this research are non financial companies listed in Indonesian Stock Exchange during period 2015-2019. The samples are collected by using purposive sampling method, and there are 44 companies selected as final samples. The hypothesis in this research is tested by using multiple regression analysis. The result of this research shows that profitability, leverage, liquidity, company growth, and earnings management had influence on firm value. While firm size, dividend policy, tangibility, institutional ownership, and managerial ownership had no influence on firm value.